Electrostimulation recovery-related strategies - Are they effective? - Maffiuletti, N. A.; Dupont, G. (ASPETAR Sports Medicine Journal, 2015)
Transcutaneous electrical stimulation (ES) consists of delivering small electrical pulses via electrodes that are positioned on the skin, usually around skeletal muscle motor points or painful body areas. Depending on electrical current (frequency and intensity) and electrode characteristics (size, position), two major ES categories can be distinguished: 1. `Sensory` ES (no muscular contractions are evoked). Conventionally called transcutaneous electrical nerve stimulation. This is mainly delivered using relatively low current intensities (at or below the sensory threshold) in an attempt to relieve pain via spinal circuitry transmitting pain (gate theory) and endorphin release. 2. `Motor` ES. Conventionally called neuromuscular electrical stimulation. This elicits visible muscular contractions (stimulations are delivered at or above the motor threshold), using either tetanic or sub-tetanic stimulations, whose clinical/physiological consequences are improved neuromuscular function and enhanced peripheral blood flow.